Assistance on Professional Tour Guides and the Relationship Between the English Language Education Study Program at the University of Nias Raya with a Job as a Tour Guide - Agus Darma Yoga Pratama; Rahmat Gaho (Linguistic Community Services Journal, 2022)
The tour guide profession has become the most essential element of the tourist sector. On the other hand, Professional tour guides must undergo extensive training. Tourism has established itself as one of the most important factors for the global community, particularly for the people of South Nias, who still preserve and present natural and cultural beauty that remains intact even in the midst of modernity, alongside changes and improvements in social, cultural, and economic factors. The presence of present tourists will, of course, generate a favorable response. Thus, to prevent this from happening, a solution is needed, namely by providing teaching or socialization in the form of training of tour guide for the next generation. The community services program organized by Warmadewa University and Nias Raya University which aim to educate and increase the interest of the younger generation regarding the preservation of the tour guide and the awareness of tourism destination, this also has a relationship with cultural and linguistic aspects. Technically, the method used in this research was qualitative research through the interview stage to find out partner problems. The source of data used in this study is primary data by conducting field observations to find out the problems faced by the students of English Language Study Program in Nias Raya University. The results showed that there was an increase in understanding the tour guides profession and being able to describe instructions or tourist attractions in practice.